Toxicity, genotoxicity and proinflammatory effects of amorphous nanosilica in the human intestinal Caco-2 cell line. Issue 2 (March 2015) - Tarantini, Adeline; Lanceleur, Rachelle; Mourot, Annick; Lavault, Marie -Thérèse; Casterou, Gérald; Jarry, Gérard; Hogeveen, Kevin; Fessard, Valérie
Highlights Toxic effects of silica NPs (15 and 55 nm) were investigated in Caco-2 cells. Both NPs were localized within the cytoplasm but did not enter the nucleus. 15 nm but not 55 nm silica induced genotoxic and proinflammatory effects. Oxidative stress is likely to be involved in the genotoxic mechanism of action. SiO2 NPs may induce potential adverse effects on the intestinal epithelium in vivo.